The association between melatonin hormone and reproductive hormones in polycystic ovary syndrome: A case–control study - Ban Jabir Edan; Zahid Mohammed-Ali Kadhim (Medical Journal of Babylon)
Abstract Background: One of the common endocrine disorders is polycystic ovary syndrome (PCOS) with prevalence of about 5%–15% of women within reproductive age. It is related to androgen disturbance, obesity, and irregular menstrual cycle. Pineal gland secretes melatonin hormone, which is involved in the regulation of the circadian rhythm. Melatonin receptors in the ovary adjust sex steroid secretion. Furthermore, it is considered a strong antioxidant, which protects ovarian follicles during follicular maturation. Objectives: To evaluate the level of melatonin in patients with PCOS and its relation with reproductive hormones and anthropometric measures. Materials and Methods: A case-control study included 200 women in reproductive age (20–40 years), including 100 PCOS patients and 100 controls who appeared to be in generally good health. Anthropometric measurements were evaluated. Reproductive hormones and anti-Müllerian hormone (AMH) were evaluated using the mini VIDAS method. Human MT (Melatonin) ELISA Kit from Elabscience source (USA) was used for measuring melatonin levels. Results: Luteinizing hormone/follicle-stimulating hormone (FSH) ratio, AMH, and melatonin were significantly higher in PCOS women, whereas FSH level was significantly lower in PCOS compared with controls. There was an adverse relationship between melatonin levels with thigh circumference, waist circumference, and waist/hip ratio (P < 0.05). There was a significant adverse correlation between melatonin and testosterone hormone in PCOS patients (P < 0.05). Melatonin level showed an AUC of 0.755 at a cutoff point of 20 ng/mL and more, giving a sensitivity (78%) and specificity (75%). Conclusions: Although PCOS women had higher serum melatonin concentrations, their effect on ovarian hormones is diminished. Melatonin had a connection with androgen, and melatonin supplements may improve metabolic dysfunction in PCOS patients.